An explanation of anomalous radar propagation following thunderstorm activity - RAGHAVAN, S. (MAUSAM, 1965)
Several cases of anomalous propagation of a 3.cm radar beam observed at Madras in the rear of thunderstorms, cannot be satisfactorily explained by the process suggested by previous workers on this subject, The anomalous echoes appear to be from ground targets, obtained after partial reflection of the radar beam at a thin boundary layer between the downdraught air of the thunderstorm and the environmental air, "Sufficient refractive Index change, required to produce the reflection can occur only in cases when the down draught air is more moist than the environment, and this agrees with the observations, The mechanism suggested does not depend on the presence of rainfall at the ground.